Risk of pre‐eclampsia after gastric bypass: a matched cohort study. (7th September 2021) - Johansson, K; Wikström, A‐K; Söderling, J; Näslund, I; Ottosson, J; Neovius, M; Stephansson, O
Abstract : Objective: To investigate whether gastric bypass before pregnancy is associated with reduced risk of pre‐eclampsia. Design: Nationwide matched cohort study. Setting: Swedish national health care. Population: A total of 843 667 singleton pregnancies without pre‐pregnancy hypertension were identified in the Swedish Medical Birth Register between 2007 and 2014, of which 2930 had a history of gastric bypass and a pre‐surgery weight available from the Scandinavian Obesity Surgery Registry. Two matched control groups (pre‐surgery and early‐pregnancy body mass index [BMI]) were propensity score matched separately for nulliparous and parous births, to post‐gastric bypass pregnancies ( n pre‐surgery‐BMI = 2634:2634/ n early‐pregnancy‐BMI = 2766:2766) on pre‐surgery/early‐pregnancy BMI, diabetes status (pre‐surgery/pre‐conception), maternal age, early‐pregnancy smoking status, educational level, height, country of birth, delivery year and history of pre‐eclampsia. Main outcome measures: Pre‐eclampsia categorised into any, preterm onset (<37 +0 weeks) and term onset (≥37 +0 weeks). Results: In post‐gastric bypass pregnancies, mean pre‐surgery BMI was 42.9 kg/m 2 and mean BMI loss between surgery and early pregnancy was 14.0 kg/m 2 (39 kg). Post‐gastric bypass pregnancies had lower risk of pre‐eclampsia compared with pre‐surgery BMI‐matched controls (1.7 versus 9.7 per 100 pregnancies; hazard ratio [HR] 0.21, 95% CI 0.15–0.28) and early‐pregnancy BMI‐matched controls (1.9 versus 5.0 per 100 pregnancies; HR 0.44, 95% CI 0.33–0.60). Although relative risks for pre‐eclampsia for post‐gastric bypass pregnancies versus pre‐surgery matched controls was similar, absolute risk differences (RD) were significantly greater for nulliparous women (RD −13.6 per 100 pregnancies, 95% CI −16.1 to −11.2) versus parous women (RD −4.4 per 100 pregnancies, 95% CI −5.7 to −3.1). Conclusion: We found that gastric bypass was associated with lower risk of pre‐eclampsia, with the largest absolute risk reduction among nulliparous women. Tweetable abstract: In this large study including two comparison groups matched for pre‐surgery or early‐pregnancy BMI, gastric bypass was associated with lower risk of pre‐eclampsia. Tweetable abstract: In this large study including two comparison groups matched for pre‐surgery or early‐pregnancy BMI, gastric bypass was associated with lower risk of pre‐eclampsia. Linked article This article is commented on by R Devlieger & D Ceulemans, p. 472 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.16959 .